Characterization of VUV pulses from the short-pulse facility at DELTA and steps towards pump-probe experiments - Huck, Maryam (Technische Universität Dortmund, 2015)
The short-pulse facility at the 1.5-GeV synchrotron light source DELTA, operated by the TU Dortmund University, generates coherent VUV radiation by Coherent Harmonic Generation (CHG) as well as coherent THz pulses. The goal is to provide femtosecond coherent VUVradiation pulses for time-resolved pump-probe experiments. CHG is based on the interaction of ultrashort laser pulses with electrons in an undulator to generate synchrotron radiation pulses of similar length, but at coherent harmonics of the laser wavelength. The goals of this PhD thesis were the characterization of the CHG pulses and the preparation of the first pump-probe experiments with the new light source. The CHG pulses were characterized using different methods which are applied either at a diagnostics beamline in air (for long wavelengths of 200 nm and above) or at an evacuated VUV beamline (for 200 nm and below). The characterization includes studying the transverse and longitudinal coherence properties of the CHG pulses, the intensity of the radiation, its angular and spectral distribution, estimate of the energy modulation, and the dependence of these properties on different parameters. In order to perform pump-probe experiments, an evacuated laser beamline of 53 m length was constructed and commissioned to guide some part of the laser pulses to the experimental station at the VUV beamline. This included optimizing and focusing the laser beam, realizing the temporal and transverse overlap between pump and probe pulses, controlling and monitoring the beam position with motorized in-vacuum mirrors and diagnostics screens, and stabilizing the angle and position of the beam using an optical feedback system.
Keywords: VUV pulses; Short-pulse facility; DELTA; Pump probe experiments; 530; Synchrotron; Kohärente Strahlung